Size-scale effects in the failure mechanisms of materials and structures : proceedings of the International Union of Theoretical and Applied Mechanics (IUTAM) Symposium on Size-Scale Effects in the Failure Mechanisms of Materials and Structures, 3-7 October 1994, Politecnico di Torino, Turin, Italy /: proceedings of the International Union of Theoretical and Applied Mechanics (IUTAM) Symposium on Size-Scale Effects in the Failure Mechanisms of Materials and Structures, 3-7 October 1994, Politecnico di Torino, Turin, Italy. (2014) - Unknown
No abstract available